Mimetic desire and child violence in Rasa’s novel by Tere Liye - Lantowa, Jafar; Sudibyo, Sudibyo; Indrastuti, Novi Siti Kussuji (Universitas Ahmad Dahlan, 2025)
Child violence in educational settings is often rooted in mimetic desire, which provokes rivalry and emotional tension among students. This study investigates the dynamics of mimetic desire, rivalry, violence, and reconciliation as portrayed in Rasa, a novel by Tere Liye. Employing a descriptive qualitative approach with thematic analysis, the research applies René Girard’s theory of mimetic desire, focusing on the interconnected concepts of desire, rivalry, and reconciliation. Textual elements such as dialogue, narrative perspective, and character development are systematically examined through six analytical stages: data familiarization, coding, theme development, thematic review and coherence checking, theme definition and naming, and interpretive narrative construction. To ensure the reliability and validity of the findings, the study incorporates intra-coder consistency testing—by re-coding at different times—and peer debriefing for collaborative validation. The results reveal that Lin’s mimetic desire to emulate Jo’s academic success and social interactions with Nando leads to escalating rivalry, ultimately manifesting in conflict and interpersonal violence. This unmanaged mimetic rivalry results in emotional manipulation, symbolic violence, and social exclusion, reflecting real-world school dynamics. Significantly, Rasa also offers a narrative resolution through self-reflection and reconciliation, positioning literature not only as a mirror of school-based violence but also as a pedagogical tool. This study contributes to Indonesian literary scholarship by integrating mimetic theory into the analysis of contemporary fiction and enriches educational discourse through an empathy-driven approach to character education and conflict prevention.